Committed a love story - Gilbert, Elizabeth 1969- (Penguin Books, 2010)
The author chronicles how the U.S. government gave her and her Brazilian-born lover, Felipe, an ultimatum--marry or he cannot enter the country again--and how she tackled her fears through research and reflection on the institution of marriage.